1977
DOI: 10.1152/jappl.1977.43.5.829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased plasma fatty acids on glycogen utilization and endurance

Abstract: The purpose of this study was to test the hypothesis that increased availability of fatty acids could increase endurance by slowing the rate of glycogen depletion. Rats were given corn oil by stomach tube, and 3 h later an injection of heparin was given to raise their plasma free fatty acids (FFA). The rats with raised FFA were able to run approximately 1 h longer than otherwise comparable control animals before becoming exhausted (181 +/- 8 vs. 118 +/- 8 min, P less than 0.001). At the point of exhaustion, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
2
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 0 publications
8
69
2
2
Order By: Relevance
“…High-fat diet can serve to increase the duration of moderate physical activity by sparing glycogen, the depletion of which is considered to be a cause of fatigue. 42 However, as HR mice do not seem to deplete liver or muscle glycogen to any greater extent than C mice when fed standard rodent chow, 9 this explanation seems unlikely for these wheel-running results. Nor does the WD's added sucrose seem likely to have any exercise-stimulating effects; when administered sucrose-based drinking solutions, both HR and C mice drank considerably more (compared with water), but showed no change in wheel running (EM Kolb and T Garland, unpublished results).…”
Section: Discussionmentioning
confidence: 93%
“…High-fat diet can serve to increase the duration of moderate physical activity by sparing glycogen, the depletion of which is considered to be a cause of fatigue. 42 However, as HR mice do not seem to deplete liver or muscle glycogen to any greater extent than C mice when fed standard rodent chow, 9 this explanation seems unlikely for these wheel-running results. Nor does the WD's added sucrose seem likely to have any exercise-stimulating effects; when administered sucrose-based drinking solutions, both HR and C mice drank considerably more (compared with water), but showed no change in wheel running (EM Kolb and T Garland, unpublished results).…”
Section: Discussionmentioning
confidence: 93%
“…In examining the effects of a LCD on exercise performance, a few animal studies have demonstrated that increased availability of fatty acids delays the development of exhaustion in rats subjected to prolonged exercise [24,25]. This has led investigators to examine differing amounts of carbohydrate intake on human performance outcomes.…”
Section: Exercise Performancementioning
confidence: 99%
“…Insulin concentrations were higher than in the starved rats; but, as in the latter, they tended to be decreased Muscle and liver glycogen. The finding that an artificial increase in plasma non-esterified fatty acids diminishes muscle glycogen depletion during exercise has been used as evidence that the glucose-fatty acid cycle operates in skeletal muscle ofexercising humans and rodents (Rennie Costill et al, 1977;Hickson et al, 1977). In keeping with such a notion, treadmill exercise caused significant decreases in the glycogen content of the soleus and the red portion of the gastrocnemius in fed rats, but not in starved rats (Table 4).…”
mentioning
confidence: 97%
“…As muscle glycogen depletion is associated with the onset of fatigue, previous investigators have examined the effect of artificially increasing plasma non-esterified fatty acids by a fat meal plus heparin on the exercise-induced depletion of glycogen in skeletal muscle. Such procedures have been showni to diminish muscle glycogen depletion and increase endurance during exercise in both humans and rodents (Rennie et al, 1976;Costill et al, 1977;Hickson et a-., 1977). Interpretation of these results is complicated, because such feeding regimens tend to increase plasma insulin.…”
mentioning
confidence: 99%